The man in the ant hill - Castro, Nachie; Yost, Christopher (New York : Marvel, 2013)
Dr. Pym must call upon his alter ego, Ant-Man, to protect vibranium when he realizes that the villain Klaw knows the serect power of the rare metal.
At head of title: "The Avengers."
Reprint. Originally published: 2011.
Keywords: Avengers (Fictitious characters) -- Fiction; Superheroes -- Fiction; Scientists -- Fiction; Avengers (Fictional characters) -- Fiction; Superheroes -- Fiction; Scientists -- Fiction; Radio and television novels